2009
DOI: 10.1093/cvr/cvp332
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer vasculature via endoglin/CD105: a novel antibody-based diagnostic and therapeutic strategy in solid tumours

Abstract: Endoglin/CD105 is well acknowledged as being the most reliable marker of proliferation of endothelial cells, and it is overexpressed on tumour neovasculature. Our current knowledge of its structure, physiological role, and tissue distribution suggests that targeting of endoglin/CD105 is a novel and powerful diagnostic and therapeutic strategy in human malignancies, through the imaging of tumour-associated angiogenesis and the inhibition of endothelial cell functions related to tumour angiogenesis. Among biothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(167 citation statements)
references
References 96 publications
(147 reference statements)
3
159
0
5
Order By: Relevance
“…As the TGF-β accessory receptor III, CD105 promotes neovascularization by binding with TGF-β1 and TGF-β3 with high affinity as reported by Fonsatti et al (36) and Warrington et al (37).…”
Section: Discussionmentioning
confidence: 65%
“…As the TGF-β accessory receptor III, CD105 promotes neovascularization by binding with TGF-β1 and TGF-β3 with high affinity as reported by Fonsatti et al (36) and Warrington et al (37).…”
Section: Discussionmentioning
confidence: 65%
“…Such a correlation for endothelial cells but not for tumor cells has also been identified in oral squamous cell carcinoma, 8,34 where in vitro studies further demonstrated that BCL2 8 In xenografted squamous cell carcinoma cell lines, BCL2 crosstalk between endothelial and tumor cells through VEGFA leads to tumor growth and metastatic development. 8,9,11,35 A neoangiogenic subtype of endothelial cells, expressing CD105, a TGFb-receptor type III auxiliary receptor, 13 has been identified. [36][37][38] CD105 expression on endothelial cells is related to tumor progression in squamous cell carcinoma, 16 glioblastomas, 15 and meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…12 Neoangiogenic endothelial cells can be characterized in solid tumor by expression of CD105, a TGFbR type III auxiliary receptor. 13 In meningiomas, glioblastomas, and squamous cell carcinoma, CD105 expression on endothelial cells is related to neoangiogenesis and to tumor progression. [14][15][16] CD105 is also expressed by endothelial cells in the primary central nervous system lymphomas and correlates with survival.…”
mentioning
confidence: 99%
“…Ya-Kai Huang 1 *, Hong Liu 2 , Xin-Zheng Wang 3 , Shan Zhu 3 angiogenesis (Fonsatti et al, 2010;Fujiwara et al, 2013). Immunostaining of CD105 is used to label MVD.…”
Section: Annexin A2 and Cd105 Expression In Pancreatic Ductal Adenocamentioning
confidence: 99%